Sosialisasi Penanaman Karakter Nilai-Nilai Cinta Tanah Air di Desa Bulan Wonosari Klaten - Apriliani, Elina Intan; Anshory, Muhammad Isa; Nashir, Muhammad Ja’far; Ningsih, Sintia Sulistia; Allaily, Nada Rihadatul Aisy; Utama, Ferdian (CV. Creative Tugu Pena, 2024)
This community service activity was conducted for PKK members in Bulan village, Wonosari district, Klaten. The purpose of holding this community service activity is to instill character in an effort to instill a sense of love for the homeland. Therefore, we intend to conduct community service activities. With the hope that it can provide additional knowledge to PKK members to become agents of change in fostering a sense of nationalism and concern for the country. And can increase the awareness of the importance of the role of each individual, especially among the Z generation in building and protecting the homeland, and encourage active participation in social, cultural and community activities. It can also strengthen the values of togetherness, unity, and the spirit of gotong royong in the community of Bulan Village. Method The approach of this community service activity entitled